Replacement of Two Failed Indirect Restorations with Direct Bonded Restorations Using Minimally Invasive Strategy - Kusumasari, Citra; Hatayama, Takashi; Shimada, Yasushi (UI Scholars Hub, 2021)
Deciding on what treatment (repair or replacement) to provide for a failed indirect restoration can be challenging. Notably, the strength of the residual tooth structure could be improved after replacing the failed indirect restoration using a minimally invasive strategy. Objective: To describe the use of a minimally invasive strategy for the successful clinical replacement of two failed indirect metal restorations with direct composite restorations and the attainment of bonded restoration. Case Report: Case 1. A 52-year-old male patient came to the dental hospital complaining of discomfort when drinking cold beverages and food impaction on the proximal area of the upper left first molar. Case 2. A 45-year-old female patient complained about her debonded metal onlay and secondary caries in the upper right second molar. Both of these indirect restoration failures were treated with direct resin composite restoration. Both patients were highly satisfied with the results. Conclusion: This report presents the benefits of adopting a minimally invasive strategy approach for replacing failed indirect restorations (inlays and onlays) with direct-bonded composite restorations. Minimally invasive direct restorations are designed to maximize the preservation of tooth structure, thereby ensuring a long-term bonded restoration and leaving future options open when a failure occurs.